In-situ composite FeS / C negative electrode material, preparation method and application thereof

CN122940209APending Publication Date: 2026-10-20GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611152660.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种原位复合FeS/C负极材料及其制备方法和应用,旨在解决现有FeS负极材料在钠离子电池应用中存在的本征电子电导率低、充放电过程中体积效应显著以及快充性能不足等技术瓶颈

Benefits of technology

(1)本发明通过分子级原位负载策略,实现FeS在碳基体中的高度均匀分散。采用吡咯作为碳源,利用Fe3+在冰浴条件下氧化引发吡咯原位聚合,将铁源均匀锚定于聚吡咯骨架中,实现了铁源在聚合物基体中的分子级分散;随后通过一步热处理同时实现聚吡咯的碳化和铁源的硫化,聚吡咯原位转化成的氮掺杂碳基体有效抑制了FeS颗粒的团聚和过度生长。该原位负载-转化策略避免了传统外加碳源与活性物质物理混合带来的分布不均和界面相容性差的问题,保证了最终复合材料中FeS在碳基体中的高度均匀分散。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of sodium-ion battery anode materials and fast-charging technology, and particularly to an in-situ composite FeS / C anode material, its preparation method, and its application. The invention involves mixing an iron salt solution and pyrrole monomers, followed by an in-situ oxidative polymerization reaction to obtain an in-situ iron-loaded polypyrrole precursor. A sulfur source is placed upstream of the gas flow in a heating device, and the in-situ iron-loaded polypyrrole precursor is placed downstream of the gas flow in the heating device. Under an inert atmosphere, a sulfidation-carbonization treatment is performed to obtain the in-situ composite FeS / C anode material. The resulting material consists of a three-dimensional continuous interconnected framework structure formed by the cross-linking of near-spherical nanoparticles with a diameter of 100–200 nm, which effectively shortens the ion diffusion path and mitigates volume changes during charging and discharging. As a sodium-ion battery anode, it exhibits excellent fast-charging performance and cycle stability, overcoming the technical bottleneck of generally poor rate performance in conversion-type anode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of sodium-ion battery anode materials and fast charging technology, and particularly to an in-situ composite FeS / C anode material, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries (SIBs) are considered a promising new energy storage system to supplement or replace lithium-ion batteries due to the abundance, wide distribution, and low cost of sodium resources and their suitable redox potential. However, sodium ions have a large radius (1.02 Å), resulting in slow diffusion kinetics in electrode materials, especially in high-rate fast-charging applications, where this bottleneck becomes more pronounced. Therefore, there is an urgent need to develop high-performance anode materials that combine high specific capacity with fast ion / electron transport capabilities. Among numerous candidate anode materials, ferrous sulfide (FeS), as a typical conversion-type anode material, is favored due to its high theoretical specific capacity (approximately 609 mAh g⁻¹). -1 With its advantages of abundant resources, low cost, and environmental friendliness, FeS anode has shown significant application potential in the field of sodium-ion batteries. However, FeS anode faces two major technical bottlenecks in practical applications: (1) low intrinsic electronic conductivity, which leads to slow charge transport dynamics and severely restricts its rate performance; (2) sodium deintercalation / intercalation based on conversion reaction mechanism, accompanied by significant volume changes during charge and discharge, which easily causes electrode structure pulverization and active material shedding, resulting in rapid decay of cycle stability.

[0003] Nanoscale composites of FeS with conductive carbon-based materials to construct three-dimensional conductive networks and stress-buffering structures are one effective strategy to overcome the aforementioned challenges. This strategy, through carbon layer coating or embedding FeS nanoparticles into a carbon matrix, can significantly improve the overall electron transport efficiency of the material and utilize the structural flexibility of the carbon skeleton to buffer the volume change stress generated during charge and discharge, thereby effectively improving electrode structural stability and cycle life. Further introducing porous structures can shorten ion diffusion paths, improve electrolyte wetting ability, and enhance interfacial reaction kinetics, achieving synergistic optimization of rate performance and cycle stability. Based on these strategies, researchers have developed various FeS / C composite anode materials, such as three-dimensional silver ear-shaped FeS / C microspheres and porous composite materials with FeS nanoparticles embedded in carbon nanosheets, which have achieved significant improvements in electrochemical performance.

[0004] However, existing methods for preparing FeS / C composite materials still have significant limitations. Most studies rely on multi-step synthetic routes, involving complex processes such as stepwise preparation of precursors, multiple heat treatments, or subsequent coatings, resulting in high energy consumption and hindering large-scale production and cost control. Furthermore, the uniformity of FeS dispersion in the carbon matrix, the flexible control of loading, and the robust interfacial bonding still require further optimization to achieve precise construction of the composite material structure at the molecular or atomic scale. Therefore, there is an urgent need to develop a simple, efficient, and scalable in-situ composite strategy to achieve uniform dispersion and robust anchoring of FeS nanoparticles in a carbon matrix, thereby simultaneously improving the material's electronic conductivity, structural stability, and sodium storage performance, and promoting the practical application of FeS-based anode materials in sodium-ion batteries. Summary of the Invention

[0005] The purpose of this invention is to provide an in-situ composite FeS / C anode material, its preparation method, and its application, aiming to solve the technical bottlenecks of existing FeS anode materials in sodium-ion battery applications, such as low intrinsic electronic conductivity, significant volume effect during charging and discharging, and insufficient fast-charging performance.

[0006] The core technical approach of this invention lies in achieving molecular-level uniform loading of the iron source in a polypyrrole matrix through in-situ oxidative polymerization of pyrrole and soluble iron salt under ice bath conditions. Following a heat treatment step, the carbonization of the polypyrrole and the in-situ sulfidation of the iron source are simultaneously completed, resulting in a composite anode material in which FeS nanocrystals are uniformly dispersed in a nitrogen-doped porous carbon matrix. This structure effectively buffers the volume change stress caused by the conversion reaction and constructs a high-speed electron / ion dual continuous transport channel, thereby synergistically improving the rate performance and cycle stability of the material.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: One of the technical solutions of this invention provides a method for preparing an in-situ composite FeS / C anode material, characterized by comprising the following steps: (1) Mix iron salt solution and pyrrole monomer and carry out in-situ oxidative polymerization reaction to obtain polypyrrole precursor with iron source in situ; (2) The sulfur source is placed upstream of the gas flow of the heating device, and the polypyrrole precursor with the iron source loaded in situ is placed downstream of the gas flow of the heating device. Under an inert atmosphere, the sulfurization-carbonization treatment is carried out to obtain the in situ composite FeS / C anode material.

[0008] The second technical solution of the present invention provides an in-situ composite FeS / C anode material prepared by the above-mentioned preparation method.

[0009] The third technical solution of the present invention provides a fast-charging sodium-ion battery comprising the above-mentioned in-situ composite FeS / C anode material.

[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves highly uniform dispersion of FeS in a carbon matrix through a molecular-level in-situ loading strategy. Pyrrole is used as the carbon source, utilizing Fe... 3+ Oxidation-induced in-situ polymerization of pyrrole under ice bath conditions uniformly anchors the iron source within the polypyrrole framework, achieving molecular-level dispersion of the iron source in the polymer matrix. Subsequently, a one-step heat treatment simultaneously carbonizes the polypyrrole and sulfides the iron source. The nitrogen-doped carbon matrix formed by the in-situ conversion of polypyrrole effectively suppresses the aggregation and excessive growth of FeS particles. This in-situ loading-conversion strategy avoids the uneven distribution and poor interfacial compatibility problems caused by the physical mixing of traditional external carbon sources and active materials, ensuring a highly uniform dispersion of FeS in the carbon matrix of the final composite material.

[0011] (2) The in-situ composite FeS / C anode material obtained by the present invention has the following significant structural advantages: (i) The three-dimensional continuous carbon skeleton network provides a high-speed transmission channel for electrons; (ii) The nanoscale FeS particles greatly shorten the solid-phase diffusion path of sodium ions, so that the sodium storage behavior exhibits pseudocapacitive characteristics controlled by the near surface; (iii) The in-situ confined coating and firm interface anchoring of FeS nanocrystals by the carbon matrix can effectively buffer the volume change stress during the charging and discharging process and inhibit the pulverization and shedding of active materials; (iv) The nitrogen-doped porous carbon matrix provides abundant active sites for sodium storage and chemically anchors polysulfide intermediates, inhibiting the shuttle effect. Therefore, when used as the anode of sodium-ion batteries, this material has significant advantages in both capacity output and cycle stability at ultra-high rates: the reversible specific capacity is as high as 636.7 mAh / g at 0.1 A / g; it still maintains an excellent capacity of 303.3 mAh / g at an ultra-high current density of 50 A / g; and the capacity retention rate is as high as 95.6% after 1200 cycles at 20 A / g, proving the key role of in-situ composite structure design in achieving fast charging performance.

[0012] (3) This invention uses widely available and inexpensive basic chemical raw materials (ferric chloride, pyrrole, thiourea, etc.), and the reaction conditions are mild (ice bath polymerization, inert atmosphere heat treatment). It does not require expensive or highly toxic reagents, nor does it have complicated post-processing procedures. It meets the requirements of green chemistry and sustainable development and has good prospects for industrial application. Attached Figure Description

[0013] Figure 1 The images shown are scanning electron microscope (SEM) images of the in-situ composite FeS / C anode material prepared in Example 1 at different magnifications, where Figure a is a low-magnification image and Figure b is a high-magnification image. Figure 2The image shows the elemental distribution of the in-situ composite FeS / C anode material prepared in Example 1. Figure 3 The images are transmission electron microscope (TEM) images of the in-situ composite FeS / C anode material prepared in Example 1 at different magnifications, where (a) is a low-magnification image and (b) is a high-magnification image. Figure 4 The X-ray diffraction (XRD) patterns of the materials prepared in Examples 1-7 and Comparative Examples 1-4 are shown, where (a) is the in-situ composite FeS / C anode material prepared in Examples 1-7, and (b) is the anode material prepared in Comparative Examples 1-4. Figure 5 Raman spectra of the carbon component in the in-situ composite FeS / C anode materials prepared in Examples 1-7; Figure 6 Thermogravimetric (TG) curves of the in-situ composite FeS / C anode materials prepared in Examples 1-3; Figure 7 The nitrogen isothermal adsorption-desorption curves and corresponding specific surface area histograms of the in-situ composite FeS / C anode materials prepared in Examples 1-7 are shown, where (a) is the nitrogen isothermal adsorption-desorption curve and (b) is the specific surface area histogram. Figure 8 Nitrogen isothermal adsorption-desorption curves of the non-in-situ composite FeS / C anode material prepared in Comparative Example 3 and the pure sulfur-doped carbon anode material prepared in Comparative Example 4. Figure 9 The first three cyclic voltammetry (CV) curves of the in-situ composite FeS / C anode material prepared in Example 1 when used as an anode in a sodium-ion battery at a current density of 0.1 A / g. Figure 10 The first three charge-discharge curves of the in-situ composite FeS / C anode material prepared in Example 1 when used as a sodium-ion battery anode under a current density of 0.1 A / g. Figure 11 The graphs show the rate performance of the negative electrode materials prepared in Examples 1-7, Comparative Examples 3 and 4 when used in sodium-ion batteries. Among them, (a) is the rate performance of the in-situ composite FeS / C negative electrode material prepared in Examples 1-7, and (b) is the rate performance of the non-in-situ composite FeS / C negative electrode material prepared in Comparative Example 3 and the pure sulfur-doped carbon negative electrode material prepared in Comparative Example 4. Figure 12 The in-situ composite FeS / C anode material prepared in Examples 1-3 is used as a sodium-ion battery anode, and its cycling stability is shown in the figure at a current density of 1 A / g. Figure 13The in-situ composite FeS / C anode material prepared in Examples 1-3 is used as a sodium-ion battery anode, and the cycle stability is shown in the figure at a current density of 20 A / g. Figure 14 The in-situ composite FeS / C anode material prepared in Example 1 is used as a sodium-ion battery anode, and its cycling stability is shown in the figure at a current density of 50 A / g. Detailed Implementation

[0014] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0015] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0016] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0017] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.

[0018] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0019] All raw materials used in this invention can be obtained commercially or prepared using existing technologies.

[0020] This invention provides an in-situ composite FeS / C anode material and its preparation method. The method first involves in-situ chemical oxidative polymerization of pyrrole in an aqueous ferric chloride solution to obtain a polypyrrole precursor uniformly loaded with an iron source. Subsequently, under an inert atmosphere, using thiourea as a sulfur source, a one-step gas-phase sulfidation-carbonization simultaneous treatment is performed. While the precursor carbonizes to form a nitrogen-doped porous carbon matrix, FeS nanocrystals are generated in-situ and confined within this carbon matrix, thereby obtaining the in-situ composite FeS / C anode material. By adjusting process parameters such as the amount of ferric chloride hexahydrate, the amount of thiourea, and the sulfidation-carbonization temperature, the structure of the in-situ iron-loaded polypyrrole precursor can be flexibly controlled, thereby achieving regulation of the final composite material's microstructure and electrochemical performance.

[0021] This invention provides a method for preparing an in-situ composite FeS / C anode material, comprising the following steps: (1) Mix iron salt solution and pyrrole monomer and carry out in-situ oxidative polymerization reaction to obtain polypyrrole precursor with iron source in situ; (2) The sulfur source is placed upstream of the gas flow of the heating device, and the polypyrrole precursor with the iron source loaded in situ is placed downstream of the gas flow of the heating device. Under an inert atmosphere, the sulfurization-carbonization treatment is carried out to obtain the in situ composite FeS / C anode material.

[0022] Step (1) of this invention involves adding pyrrole monomer to an iron salt solution and carrying out an in-situ oxidative polymerization reaction under ice bath and stirring conditions. After the reaction is completed, the mixture is directly dried to obtain a polypyrrole precursor with an in-situ supported iron source.

[0023] In this invention, the iron salt solution includes ferric chloride solution or ferric nitrate solution; the concentration of the iron salt solution is 0.3 to 0.6 mol / L, for example, it can be 0.3 mol / L, 0.4 mol / L, 0.5 mol / L or 0.6 mol / L, etc.

[0024] In this invention, the amount and concentration of iron salt directly affect the degree of polymerization of polypyrrole and the uniformity of iron source loading. 3+ By controlling the concentration within this range, it is possible to ensure a sufficient supply of Fe. 3+ This can initiate the full polymerization of pyrrole to form a structurally complete polypyrrole carbon source precursor; on the other hand, it can avoid the excessive iron content in the precursor due to excessive iron source, which would lead to the formation of excessive FeS particle agglomeration after heat treatment and destroy the continuity of the carbon skeleton structure.

[0025] In a preferred embodiment of the present invention, the ferric chloride solution is a ferric chloride hexahydrate solution; the ferric nitrate solution is a ferric nitrate nonahydrate solution.

[0026] In a preferred embodiment of the present invention, the iron salt solution is obtained by adding soluble iron salt to deionized water and stirring to dissolve it under ice bath conditions; the temperature of the ice water bath is 0~5℃ and the stirring speed is 300rpm.

[0027] In this invention, the molar ratio of the pyrrole monomer to the iron ions in the iron salt solution is 1:1.5 to 2.5, for example, it can be 1:1.5, 1:1.8, 1:2, 1:2.2 or 1:2.5, etc.

[0028] In this invention, pyrrole is used as a carbon source, which reacts with Fe... 3+ The molar ratio is a key parameter for controlling the composition of the precursor and the carbon / ferrous sulfide ratio in the final composite material. When the molar ratio is controlled within the range of 1:(1.5~2.5), Fe... 3+ It can meet the stoichiometric requirements of oxidative polymerization of pyrrole and ensure that a sufficient amount of iron source is uniformly loaded in the polypyrrole skeleton.

[0029] In this invention, the temperature of the in-situ oxidative polymerization reaction is 0~5℃ and the time is 4~8h, for example, it can be 4h, 5h, 6h, 7h or 8h, etc.

[0030] In a preferred embodiment of the present invention, the in-situ oxidative polymerization reaction is carried out under stirring at a speed of 300 rpm.

[0031] In this invention, the oxidative polymerization of pyrrole is an exothermic reaction. Conducting it under ice-bath conditions effectively controls the polymerization rate, preventing rapid cross-linking and aggregation of the polypyrrole chains due to localized overheating, thus ensuring uniform dispersion of the iron source in the polypyrrole matrix. Controlling the reaction temperature within the range of 0–5 °C allows the polymerization reaction to proceed gently and steadily. If the reaction time is too short, the pyrrole polymerization is incomplete, resulting in a low and unevenly distributed iron source loading rate; if the reaction time is too long, the polymerization product may undergo excessive cross-linking, increasing the difficulty of subsequent carbonization and energy consumption. This temperature and time range ensures that the polymerization reaction is fully completed, obtaining a polypyrrole precursor with a uniform composition and stable structure and an in-situ loaded iron source.

[0032] In a preferred embodiment of the present invention, the drying temperature is 80°C and the drying time is 24 hours.

[0033] Step (2) of this invention involves grinding the polypyrrole precursor with an in-situ iron source into powder, placing the polypyrrole precursor powder with an in-situ iron source and the sulfur source in two containers respectively, with the sulfur source placed upstream of the heating device and the polypyrrole precursor powder with an in-situ iron source placed downstream of the heating device in the reaction zone, and performing sulfidation-carbonization treatment under an inert atmosphere, and then naturally cooling to room temperature to obtain the in-situ composite FeS / C anode material.

[0034] In a preferred embodiment of the present invention, the heating device is preferably a tubular furnace.

[0035] In this invention, the sulfur source includes one or more of thiourea, thioacetamide, sodium thiosulfate, and ammonium persulfate.

[0036] In this invention, the mass ratio of the polypyrrole precursor to the sulfur source in the in-situ loaded iron source is 1:1.5 to 3.5, for example, it can be 1:1.5, 1:2, 1:2.5, 1:3 or 1:3.5, etc.

[0037] In this invention, thiourea decomposes during heat treatment, releasing active sulfur species that react with the iron source supported in the polypyrrole framework to generate FeS. If the amount of thiourea is too small, the iron source will not be fully sulfidated, resulting in residual iron oxide impurities in the product, affecting material purity and electrochemical performance. If the amount of thiourea is too large, it may lead to over-sulfidation of the iron source, generating sulfur-containing impurities. Furthermore, the pyrolysis of excessive thiourea increases the production of corrosive gases such as hydrogen sulfide, reducing material purity and potentially causing excessive etching of the carbon framework. By controlling the mass ratio within this range, the iron source can be fully converted into pure-phase FeS while avoiding excessive etching of the carbon framework by excessive thiourea, resulting in a pure, structurally complete in-situ composite FeS / C anode material.

[0038] In this invention, the heating rate of the sulfidation-carbonization treatment is 5~10℃ / min, for example, it can be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min or 10℃ / min, etc., the temperature is 700~900℃, for example, it can be 700℃, 750℃, 800℃, 850℃ or 900℃, etc., and the time is 2~4h, for example, it can be 2h, 3h or 4h, etc.

[0039] In this invention, the heating rate is a crucial factor affecting the precursor carbonization process and the microstructure of the product. If the heating rate is too slow, the heat treatment cycle is prolonged and energy consumption increases; if the heating rate is too fast, the organic components inside the precursor decompose violently, generating a large amount of gas, which can easily lead to material structure collapse or the formation of through cracks. Simultaneously, FeS grains tend to grow abnormally during rapid heating. The heat treatment temperature is a core parameter determining the purity, crystallinity, and graphitization degree of the carbon skeleton in FeS. Below 700 °C, polypyrrole carbonization is insufficient, the carbon skeleton has poor conductivity, and the FeS crystallinity is low, resulting in poor electrochemical performance. Above 900 °C, FeS grains grow significantly, the layered structure thickens, and excessive graphitization of the carbon skeleton leads to a decrease in specific surface area and a reduction in active sites.

[0040] In this invention, the inert atmosphere is at least one of argon, nitrogen, or helium; the gas flow rate of the inert atmosphere is 10~50 mL / min.

[0041] In this invention, an inert atmosphere effectively isolates oxygen, preventing the carbon skeleton from oxidizing and ablating at high temperatures and the FeS from oxidizing and deteriorating, thus ensuring product purity and structural integrity. Controlling the gas flow rate within the aforementioned range ensures rapid atmosphere replacement within the furnace tube and timely discharge of byproduct gases, while avoiding physical disturbance to the sample or temperature fluctuations within the furnace, which is beneficial for obtaining products with uniform structure and stable performance.

[0042] The present invention also provides an in-situ composite FeS / C anode material prepared by the above-described preparation method.

[0043] In this invention, the in-situ composite FeS / C anode material is a three-dimensional continuous interconnected framework structure formed by the cross-linking of spherical nanoparticles. The spherical nanoparticles are a composite structure in which FeS nanocrystals are uniformly dispersed and in situ confined in a carbon matrix, and the particle surface has a rough, bumpy, wrinkled core-shell morphology. The carbon matrix is ​​nitrogen-doped amorphous porous carbon, wherein the nitrogen element is derived from in-situ doping of the polypyrrole precursor.

[0044] In this invention, the diameter of the spherical nanoparticles is 100~200 nm; the interior is an in-situ composite structure in which FeS nanocrystals are uniformly dispersed in a carbon matrix, and the surface of the particles has a rough, bumpy, wrinkled core-shell morphology. The FeS nanocrystals are hexagonal FeS, in-situ coated and anchored by a carbon matrix, effectively suppressing particle agglomeration and structural pulverization during charging and discharging; the specific surface area of ​​the in-situ composite FeS / C anode material is 43~141 m². 2 / g, the BET specific surface area can be controlled by the preparation process parameters; the mass content of the FeS nanocrystals in the composite material is 80%~92%.

[0045] The present invention also provides a fast-charging sodium-ion battery comprising the above-mentioned in-situ composite FeS / C anode material.

[0046] This invention initiates in-situ polymerization of pyrrole and achieves uniform molecular-level anchoring of iron ions within the polypyrrole molecular chains. A single high-temperature treatment simultaneously completes polypyrrole carbonization, iron source sulfidation, and nitrogen doping of the carbon matrix, ensuring uniform dispersion of FeS nanocrystals within the carbon matrix. The resulting material consists of a three-dimensional, continuously interconnected framework structure formed by the cross-linking of 100–200 nm diameter spherical nanoparticles, effectively shortening the ion diffusion path and mitigating volume changes during charge and discharge. As a sodium-ion battery anode, it exhibits excellent fast-charging performance and cycle stability, overcoming the technical bottleneck of generally poor rate performance in conversion-type anode materials.

[0047] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0048] Example 1 (1) Add 22.20 mmol of ferric chloride hexahydrate FeCl3·6H2O to 40 mL of deionized water and stir at 300 rpm under ice bath conditions of 0~5 ℃ to dissolve it, thus obtaining an aqueous solution of FeCl3; (2) 9.20 mmol of pyrrole monomer was added dropwise to the FeCl3 aqueous solution obtained in step (1), and the polymerization reaction was carried out by stirring at 300 rpm for 5 h under ice bath conditions of 0~5 ℃. After the reaction was completed, the resulting mixture was transferred to an evaporating dish and dried in an oven at 80 ℃ for 24 h to obtain the polypyrrole precursor with an in-situ supported iron source, denoted as Fe-PPY; (3) Grind the precursor obtained in step (2) into powder, and place 1 g of precursor and 2.5 g of thiourea in two corundum boats respectively. The thiourea is placed upstream of the gas flow in the tube furnace as a sulfur source, and the precursor is placed downstream of the gas flow in the reaction zone. High-purity argon gas is introduced at a rate of 40 mL / min for protection. The temperature is raised to 700 ℃ at a rate of 10 ℃ / min and held for 2 hours for sulfidation-carbonization treatment. After natural cooling to room temperature, the in-situ composite FeS / C anode material is obtained, which is denoted as FeS / C-1.

[0049] Example 2 The only difference from Example 1 is that the sulfidation-carbonization temperature in step (3) is adjusted from 700 °C to 800 °C. All other conditions are the same as in Example 1, and the resulting product is denoted as FeS / C-2.

[0050] Example 3 The only difference from Example 1 is that the sulfidation-carbonization temperature in step (3) is adjusted from 700 °C to 900 °C. All other conditions are the same as in Example 1, and the resulting product is denoted as FeS / C-3.

[0051] Example 4 The only difference from Example 1 is that the amount of thiourea in step (3) is adjusted from 2.5 g to 2 g. All other conditions are the same as in Example 1, and the resulting product is denoted as FeS / C-4.

[0052] Example 5 The only difference from Example 1 is that the amount of thiourea in step (3) is adjusted from 2.5 g to 3 g. All other conditions are the same as in Example 1, and the resulting product is denoted as FeS / C-5.

[0053] Example 6 The only difference from Example 1 is that the amount of ferric chloride hexahydrate in step (1) was adjusted from 22.20 mmol to 13.43 mmol. All other conditions were the same as in Example 1, and the resulting product was denoted as FeS / C-6.

[0054] Example 7 The only difference from Example 1 is that the amount of ferric chloride hexahydrate in step (1) was adjusted from 22.20 mmol to 17.90 mmol. All other conditions were the same as in Example 1, but the amounts were different. The resulting product was denoted as FeS / C-7.

[0055] Comparative Example 1 The only difference from Example 1 is that the amount of thiourea used in step (3) is further reduced to 1 g, while the other conditions are the same as in Example 1, causing partial sulfidation of the iron source into FeO. x / FeS composite phase.

[0056] Comparative Example 2 The only difference from Example 1 is that the amount of thiourea in step (3) is further increased to 4 g, while the other conditions are the same as in Example 1, so that the iron source undergoes excessive sulfidation to form an S / FeS composite phase.

[0057] Comparative Example 3 This comparative example provides a method for preparing an in-situ composite FeS / C anode material, including the following steps: (1) Add 22.20 mmol of ferric chloride hexahydrate FeCl3·6H2O to 40 mL of deionized water and stir at 300 rpm under ice bath conditions of 0~5 ℃ to dissolve it, thus obtaining an aqueous solution of FeCl3; (2) 9.20 mmol of pyrrole monomer was added dropwise to the FeCl3 aqueous solution obtained in step (1), and the polymerization reaction was carried out by stirring at 300 rpm for 5 h under ice bath conditions of 0~5 ℃. After the reaction was completed, an appropriate amount of deionized water was added to the resulting mixture to wash and purify the system, and the product was collected by centrifugation. The precipitate was placed in an oven and dried at 80 ℃ for 24 h to obtain an iron-free polypyrrole precursor, denoted as PPY. (3) Grind the precursor obtained in step (2) into powder, weigh 0.5 g of the precursor and mix and grind it evenly with 1.22 g of FeCl3·6H2O, place the evenly mixed precursor and 3.45 g of thiourea in two corundum boats respectively, with the thiourea placed upstream of the gas flow in the tube furnace as a sulfur source and the precursor placed downstream of the gas flow in the reaction zone, and pass high-purity argon gas through at a rate of 40 mL / min for protection, heat to 700 ℃ at a heating rate of 10 ℃ / min and hold for 2 hours for sulfidation-carbonization treatment, and after naturally cooling to room temperature, obtain the non-in-situ composite FeS / C anode material.

[0058] Comparative Example 4 This comparative example provides a method for preparing a sulfur-doped carbon anode material without FeS, comprising the following steps: (1) Add 22.20 mmol of ferric chloride hexahydrate FeCl3·6H2O to 40 mL of deionized water and stir at 300 rpm under ice bath conditions of 0-5 ℃ to obtain FeCl3 aqueous solution; (2) 9.20 mmol of pyrrole monomer was added dropwise to the FeCl3 aqueous solution obtained in step (1), and the polymerization reaction was carried out by stirring at 300 rpm for 5 h under ice bath conditions of 0-5 ℃. After the reaction was completed, an appropriate amount of deionized water was added to the resulting mixture to wash and purify the system, and the product was collected by centrifugation. The precipitate was placed in an oven and dried at 80 ℃ for 24 h to obtain an iron-free polypyrrole precursor, denoted as PPY. (3) Grind the precursor obtained in step (2) into powder, weigh 1 g of precursor and 2.5 g of thiourea and place them in two corundum boats respectively. The thiourea is placed upstream of the gas flow in the tube furnace as a sulfur source, and the precursor is placed downstream of the gas flow in the reaction zone. High-purity argon gas is introduced at a rate of 40 mL / min for protection. The temperature is raised to 700 ℃ at a rate of 10 ℃ / min and held for 2 hours for carbonization treatment. After naturally cooling to room temperature, sulfur-doped carbon anode material without FeS is obtained.

[0059] Example of effect 1 To verify the structural characteristics of the in-situ composite FeS / C anode material in this invention, the materials prepared in Examples 1-7 and Comparative Examples 1-4 were characterized and analyzed in terms of morphology, phase composition, and pore structure.

[0060] (1) Morphological structure characterization Figure 1 The images shown are scanning electron microscope (SEM) images of the in-situ composite FeS / C anode material prepared in Example 1 at different magnifications. As seen in the low-magnification image in Figure a, the obtained material consists of tightly packed, near-spherical nanoparticles. Cross-linking and fusion occur at the contact interfaces between the particles, forming a three-dimensional, continuously connected conductive framework structure. This structure is beneficial for constructing a high-speed electron transport network and provides abundant interfacial channels for sodium ion diffusion. Further, the high-magnification image in Figure b shows that the surface of individual particles exhibits fine, uneven wrinkles, possessing a rough, core-shell-like surface texture. This rough surface effectively increases the contact area between the electrode material and the electrolyte, improving the interfacial electrochemical reaction kinetics.

[0061] Figure 2The image shows the elemental distribution of the in-situ composite FeS / C anode material prepared in Example 1. As can be seen from the image, the five elements C, N, O, S, and Fe are uniformly distributed in the material. The Fe element signal and the S element signal show a high degree of spatial overlap, and their distribution areas correspond completely. This indicates that the FeS active phase is uniformly dispersed inside the nitrogen-doped carbon matrix, without obvious metal agglomeration or local segregation.

[0062] Figure 3 The images shown are transmission electron microscope (TEM) images of the in-situ composite FeS / C anode material prepared in Example 1 at different magnifications. As seen in the low-magnification image in Figure a, the material exhibits a cluster-like morphology formed by the adhesion and aggregation of numerous spherical nanoparticles. The overall particle size of each individual particle is approximately in the hundreds of nanometers range, reflecting the in-situ composite characteristics of FeS and the carbon matrix. The high-magnification image in Figure b further shows that the FeS nanocrystals are in-situ coated by the carbon layer and firmly anchored within the carbon matrix framework, forming a tight two-phase composite interface. This confirms that the iron ions in-situ loaded in the polypyrrole precursor are transformed in-situ into uniformly distributed FeS nanocrystals during the subsequent sulfidation process.

[0063] (2) Phase composition analysis Figure 4 The X-ray diffraction (XRD) patterns of the materials prepared in Examples 1-7 and Comparative Examples 1-4 are shown in Figure a. As can be seen from Figure a, the in-situ composite FeS / C anode materials prepared in Examples 1-7 exhibit characteristic diffraction peaks of hexagonal FeS (PDF#37-0477) at 2θ ≈ 18.7°, 29.9°, 33.7°, 43.1°, and 53.2°, corresponding to the (101), (110), (112), (114), and (300) crystal planes, respectively. The diffraction peaks are sharp and without obvious impurity peaks, confirming that the prepared materials have a high-purity FeS active phase. As can be seen from Figure b, in addition to the above diffraction peaks, other impurity phase diffraction peaks also appeared in the XRD patterns of the materials prepared in Comparative Examples 1 and 2, indicating that when the amount of thiourea deviates from the preferred range of the present invention, the degree of sulfidation reaction is improper: too little thiourea leads to insufficient sulfidation and the formation of FeO. x / FeS composite phase; excessive thiourea may trigger side reactions to generate inactive sulfur-containing impurities. Comparative Example 3: Fe removal from the precursor. 3+ After being ground with ferric chloride hexahydrate and sulfided, it still exhibited the characteristic diffraction peaks of FeS. Comparative Example 4, due to the removal of Fe from the precursor... 3+ The product after sulfidation treatment did not show any FeS diffraction peaks, confirming that it is a pure sulfur-doped carbon material. The above comparison results fully demonstrate that precise control of precursor composition and thiourea dosage is the key to achieving the preparation of high-purity in-situ composite FeS / C anode materials.

[0064] Figure 5The figures show the Raman spectra of the in-situ composite FeS / C anode materials prepared in Examples 1-7. As can be seen from the figures, all samples show a Raman spectrum at ~1356 cm⁻¹. -1 and ~1587 cm -1 Significant vibrational peak signals were observed, corresponding to the D peak (defects) and G peak (graphitization degree) of the carbon component, respectively. The peak shapes of the D and G peaks of each sample were highly similar, with only differences in the relative peak intensity ratio (ID / IG), indicating that the phase types of the formed carbon matrix were basically consistent. The preparation process parameters controlled the defect density and graphitization level of the carbon layer, thus providing a flexible means to optimize the conductivity and sodium storage active sites of the composite material.

[0065] Figure 6 The thermogravimetric (TG) curves of the in-situ composite FeS / C anode materials prepared in Examples 1-3 are shown in the figure. As can be seen from the figure, the three samples exhibit similar thermogravimetric behavior in air: initially, a slight weight gain occurs at low temperatures, due to the preferential oxidation of FeS with oxygen to generate oxygen-containing products such as ferrous sulfate and iron oxides, resulting in a large number of oxygen atoms bound to the solid lattice and thus increasing the mass; subsequently, a first weight loss stage occurs in the 400–500℃ range, corresponding to the decomposition of sulfate and the release of sulfur-containing gases; finally, a rapid weight loss stage occurs in the 500–670℃ range, corresponding to the oxidative decomposition of the carbon skeleton. Based on the TG curves, the mass content of FeS active material in the composite materials prepared in Examples 1-3 is approximately 80.30–91.85%, indicating that the in-situ composite strategy of this invention can achieve precise control of the loading of highly active materials, which is beneficial for balancing high energy density and excellent cycle stability.

[0066] (3) Pore structure analysis Figure 7 The figures show the nitrogen isothermal adsorption-desorption curves and corresponding specific surface area histograms of the in-situ composite FeS / C anode materials prepared in Examples 1-7. As shown in Figure a, the isothermal adsorption-desorption curves of all materials exhibit type IV adsorption characteristics, with a hysteresis loop appearing in the medium-to-high relative pressure range, indicating a well-developed mesoporous structure within the materials. The specific surface area histogram in Figure b shows that the specific surface areas of these materials range from 43.3 to 141.0 m². 2 Between / g, with Example 5 having the highest specific surface area (141 m²). 2 / g), Example 3 had the lowest specific surface area (43.3 m² / g). 2 The result ( / g) indicates that adjusting the preparation process parameters can effectively optimize the pore structure of the porous carbon matrix in the material and improve sodium storage kinetics.

[0067] Figure 8The nitrogen isotherm adsorption-desorption curves are shown for the materials prepared in Comparative Examples 3 and 4. Both groups of samples exhibit type IV isotherm adsorption curves, possessing both microporous and mesoporous structures, with specific surface areas of 181.3 and 199.1 m², respectively. 2 / g. It is worth noting that the specific surface areas of Comparative Examples 3 and 4 are significantly higher than those of the other examples. This is related to the fact that after iron ions are removed through washing during their preparation process, the remaining polypyrrole carbonizes to form richer pores. However, combined with subsequent electrochemical performance comparisons, it can be seen that an excessively high specific surface area does not necessarily correspond to excellent sodium storage performance. The embodiments of this invention achieve a balance between high FeS loading and a good conductive network at a moderate specific surface area, which is more conducive to optimizing overall electrochemical performance.

[0068] Application Example 1 To verify the electrochemical performance advantages of the in-situ composite FeS / C anode material of the present invention, the materials prepared in Examples 1-7 and Comparative Examples 3-4 were used as anode active materials for sodium-ion batteries, and coin half-cells were assembled for performance testing and verification.

[0069] (1) Preparation of battery electrode The above materials were used as negative electrode active materials and mixed with conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) at a mass ratio of 7:2:1. An appropriate amount of N-methylpyrrolidone (NMP) was added dropwise as a dispersant, and the mixture was degassed in a planetary stirrer for 30 min to form a uniformly flowing black slurry. The slurry was uniformly coated onto the surface of a copper foil current collector using a scraper and dried under vacuum at 80 °C for 8–12 h. The copper foil loaded with the slurry was then cut into electrode sheets with a diameter of 12 mm and compacted to obtain the negative electrode sheet for the sodium-ion battery.

[0070] (2) Half-cell assembly In a glove box filled with high-purity argon gas and with water and oxygen content both below 0.01 ppm, a CR2032 coin cell was assembled. The prepared dry electrode sheet was used as the working electrode, a sodium metal sheet as the counter electrode, and a glass fiber membrane (Whatman GF / D) as the separator. The electrolyte was a 1 mol / L sodium hexafluorophosphate (NaPF6) solution in dimethyl ether (DME). The negative electrode shell, spring plate, gasket, sodium sheet, electrolyte, separator, electrode sheet, and positive electrode shell were assembled sequentially, ensuring the electrolyte fully wetted the separator and electrode interface. The assembled coin cell was allowed to stand at room temperature for 8 hours to allow the electrolyte to fully penetrate the electrode materials and separator interface.

[0071] (3) Sodium-ion battery performance Figure 9The figure shows the cyclic voltammetry curves of the in-situ composite FeS / C anode material prepared in Example 1 under a current density of 0.1 A / g for the first three cycles. As can be seen from the figure, a strong reduction peak appears in the 0.9-1.0 V range during the first discharge cycle, corresponding to Na. + The process involves embedding into the FeS lattice and undergoing a conversion reaction to generate Fe and Na₂S, accompanied by an irreversible process of electrolyte reduction and decomposition on the electrode surface to form an SEI film. The broad, weak reduction peak in the 0.01–0.6 V range originates from the adsorption of sodium ions by the carbon matrix. During the subsequent charging process, the oxidation peak in the 1.2–1.4 V range corresponds to the reverse process of the conversion reaction, namely the desodium removal reaction of Na₂S and Fe oxidizing to regenerate FeS. The curves in cycles 2 and 3 highly overlap, with minimal shift in the peak positions and peak currents of the reduction and oxidation processes. This indicates that after the first cycle completes the construction of the SEI film, the FeS-based conversion-type sodium storage reaction exhibits excellent electrochemical reversibility and interfacial stability.

[0072] Figure 10 The first three cycles of constant current charge-discharge curves for the in-situ composite FeS / C anode material prepared in Example 1 are shown under a current density of 0.1 A / g. The tests were conducted at room temperature, with a voltage scan range of 0.01–3 V (vs. Na). + As shown in the figure, the material achieves a discharge specific capacity of 835.1 mAh / g and a charge specific capacity of 615.7 mAh / g, corresponding to an initial coulombic efficiency of 73.7%. The irreversible capacity loss in the first cycle mainly originates from the formation of the SEI film, a common characteristic of conversion-type anode materials. After the first cycle, the charge-discharge curve tends to stabilize, indicating that the material has a high reversible sodium storage capacity.

[0073] Figure 11Figure a shows the rate performance of the materials prepared in Examples 1-7, Comparative Examples 3 and 4 within a current density range of 0.1–50 A / g. Specific discharge capacity data are shown in Table 1. As can be seen from Figure a and Table 1, the in-situ composite FeS / C anode materials prepared in Examples 1-7 all exhibit excellent rate performance within the range of 0.1–50 A / g, especially maintaining a high specific capacity even at ultra-high rates. This fully demonstrates the outstanding advantages of the in-situ composite structure of this invention in high-rate fast charging scenarios. Example 1 exhibited the highest discharge capacity under all current gradients, reaching 636.7 mAh / g at 0.1 A / g. Even when the current density surged to 50 A / g (equivalent to approximately 8 minutes for one charge-discharge cycle), it maintained an ultra-high reversible capacity of 303.3 mAh / g, with a capacity retention rate as high as 47.6%. Furthermore, when the current density returned to 0.1 A / g, the specific capacity rapidly rebounded to 538.5 mAh / g, with a recovery rate of 84.6%, indicating that the material possesses excellent structural reversibility and rate tolerance. As shown in Figure b and Table 1, the rate performance of the non-in-situ composite FeS / C anode material prepared in Comparative Example 3 and the pure sulfur-doped carbon anode material prepared in Comparative Example 4 was significantly inferior to that of the examples. Comparative Example 3 exhibits a specific capacity of only 102.5 mAh / g at 50 A / g, significantly lower than the 303.3 mAh / g of Example 1. The fundamental reason for this performance gap lies in the fact that Comparative Example 3 uses a non-in-situ physical mixing method to introduce the iron source, resulting in larger FeS particle size, poor dispersion uniformity, and weak interfacial bonding with the carbon matrix. This leads to a longer solid-phase diffusion path for sodium ions and greater charge transport resistance, resulting in severe capacity decay under high current. This comparison directly confirms the irreplaceable nature of the "in-situ loading-in-situ sulfidation-carbonization" strategy of this invention in constructing fast-charging FeS / C composite materials. Comparative Example 4, as a pure sulfur-doped carbon material, shows a specific capacity at all current densities significantly lower than the examples containing the FeS active phase, reaching only 73.6 mAh / g at 50 A / g. Its low capacity is essentially due to the lack of a high theoretical specific capacity contribution from the FeS conversion reaction. This comparison further demonstrates that in-situ composite of the FeS active component and the carbon matrix is ​​a necessary condition for achieving a synergistic improvement in both high capacity and high rate performance.

[0074] Table 1. Discharge specific capacity of various materials at different current densities (unit: A / g) (unit: mAh / g)

[0075] (4) Cyclic stability analysis Figure 12The figure shows the cycling stability of the in-situ composite FeS / C anode materials prepared in Examples 1-3 under a current density of 1 A / g. As can be seen from the figure, Examples 1-3 all exhibit excellent cycling stability, with first-cycle coulombic efficiencies (ICE) of 72%, 71%, and 69%, respectively, and no significant capacity decay after 500 cycles. This excellent short-cycle stability is attributed to the in-situ confinement and buffering effect of the carbon matrix on the FeS nanocrystals, effectively suppressing volume expansion and active material shedding caused by the conversion reaction.

[0076] Figure 13 The figure shows the cycling stability of the in-situ composite FeS / C anode materials prepared in Examples 1-3 under an ultra-high current density of 20 A / g. As can be seen from the figure, after 1200 cycles under this extreme fast-charging condition, the discharge specific capacity of Examples 1 and 2 remained at 445.5 and 431.1 mAh / g, respectively, with capacity retention rates of 95.6% and 84.2% calculated based on the capacity after activation in cycle 6. The specific capacity of Example 3 remained at 391.7 mAh / g after 1000 cycles. Therefore, the in-situ composite FeS / C anode material prepared in this invention not only exhibits extremely high reversible specific capacity at ultra-high rates but also demonstrates excellent long-cycle structural stability, meeting the stringent requirements for long lifespan in fast-charging sodium-ion batteries.

[0077] Figure 14 The figure shows the cycling stability of the in-situ composite FeS / C anode material prepared in Example 1 at an extreme current density of 50 A / g. As can be seen from the figure, after 1000 cycles at such a high charge-discharge rate, its reversible specific capacity remains at 312.5 mAh / g, representing a capacity retention of 97.8% based on the capacity after activation in cycle 6. It is particularly noteworthy that 50 A / g corresponds to an ultra-high rate of approximately 82C (based on 609 mAh / g), meaning a theoretical charge-discharge cycle can be completed in approximately 1.5 minutes. Achieving such excellent capacity retention under these extreme conditions strongly demonstrates that the in-situ composite FeS / C anode material of this invention possesses near-surface controlled pseudocapacitive sodium storage behavior and ultrafast ion / electron transport kinetics, making it a promising fast-charging sodium-ion battery anode material for practical applications.

[0078] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing an in-situ composite FeS / C anode material, characterized in that, Includes the following steps: (1) Mix iron salt solution and pyrrole monomer and carry out in-situ oxidative polymerization reaction to obtain polypyrrole precursor with iron source in situ; (2) The sulfur source is placed upstream of the gas flow of the heating device, and the polypyrrole precursor with the iron source loaded in situ is placed downstream of the gas flow of the heating device. Under an inert atmosphere, the sulfurization-carbonization treatment is carried out to obtain the in situ composite FeS / C anode material.

2. The preparation method according to claim 1, characterized in that, The iron salt solution includes ferric chloride solution or ferric nitrate solution; the concentration of the iron salt solution is 0.3–0.6 mol / L.

3. The preparation method according to claim 1, characterized in that, The molar ratio of the pyrrole monomer to the iron ions in the iron salt solution is 1:1.5~2.

5.

4. The preparation method according to claim 1, characterized in that, The in-situ oxidative polymerization reaction is carried out at a temperature of 0~5℃ for 4~8h.

5. The preparation method according to claim 1, characterized in that, The sulfur source includes one or more of thiourea, thioacetamide, sodium thiosulfate, and ammonium persulfate.

6. The preparation method according to claim 1, characterized in that, The mass ratio of the polypyrrole precursor to the sulfur source in the in-situ loaded iron source is 1:1.5~3.

5.

7. The preparation method according to claim 1, characterized in that, The heating rate of the sulfidation-carbonization treatment is 5~10℃ / min, the temperature is 700~900℃, and the time is 2~4h.

8. An in-situ composite FeS / C anode material prepared by the preparation method according to any one of claims 1 to 7.

9. A fast-charging sodium-ion battery, characterized in that, It includes the in-situ composite FeS / C anode material as described in claim 8.